2016
DOI: 10.1227/neu.0000000000001034
|View full text |Cite
|
Sign up to set email alerts
|

Technique, Results, and Complications Related to Robot-Assisted Stereoelectroencephalography

Abstract: The robotic SEEG technique and method were demonstrated to be safe, accurate, and efficient in anatomically defining the epileptogenic zone and subsequently promoting sustained seizure freedom status in patients with difficult-to-localize seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
238
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(254 citation statements)
references
References 82 publications
10
238
2
4
Order By: Relevance
“…Thus, it can be expected that the absolute accuracy in future clinical trials will be degraded due to the above listed factors. This has already been confirmed by recent clinical case studies with the Neuromate [2] and ROSA [3], [16] robotic systems.…”
Section: Experimental Setup -Phantom Trialssupporting
confidence: 64%
“…Thus, it can be expected that the absolute accuracy in future clinical trials will be degraded due to the above listed factors. This has already been confirmed by recent clinical case studies with the Neuromate [2] and ROSA [3], [16] robotic systems.…”
Section: Experimental Setup -Phantom Trialssupporting
confidence: 64%
“…Recently, González-Martínez et al reported a median EPLE of 1.2 mm and TPLE of 1.7 mm (major bleeding: 1%) for 500 electrodes implanted at the Cleveland Clinic. 29 Moreover, the patient series by Cardinale accounted for 1050 electrodes implanted under assistance of a different robotic system and frame-based registration (EPLE: 0.78 mm, complications: 0%).…”
Section: Fig 5 A-cmentioning
confidence: 99%
“…The cortical entry point is also the most important region for safety profiles. Gonzalez-Martinez et al 12 reported a median entry point LE of 1.2 mm (IQR 0.78-1.83 mm) from 500 electrodes implanted with the ROSA robot in frameless conditions.…”
Section: Accuracy In Clinical Studies For Seegmentioning
confidence: 99%
“…1,11,12,15,25 Patient registration can be performed in frame-based or frameless conditions. Since the fall of 2008, we have used a robotic assistant in frame-based conditions for implanting all SEEG electrodes at Niguarda Hospital.…”
mentioning
confidence: 99%